The Relationship Between Promoting Post Acquisition Skills And His Veriable Residents Of The Fifth Grade - Jnad, Roaa; Barakat, Nour (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Although metacogrition is still considered some of the new structures in the search for all educators, here is the aim of our current research witch is to find realiaty relationship between promoting post acquisition skills and his veriable resident. All in order to benefit from the results in drawing the attention of the educational process in this area. According to that, the descriptive approach was adhered. So a special question are consisted of(30)items in three fields was designed for that purpose. thesample of this research was selected randomly and consisted of(132) learner of 5th in Banias. The research’s results show the learner used the planning skills as a promoting post acquisition in bad level, either the monitoring or evaluation. Where as the study doesn’t shoes any statistical differences among the average of the degrees of learners in metacognition according to the variable residents. This study recommended to establish training sessions to the learners and teachers to use metacognition to educate them and its applications in education, and to include the curricula suitable activities of this.